2020
DOI: 10.1017/s003329171900357x
|View full text |Cite
|
Sign up to set email alerts
|

Jumping to conclusions, general intelligence, and psychosis liability: findings from the multi-centre EU-GEI case-control study

Abstract: Background The ‘jumping to conclusions’ (JTC) bias is associated with both psychosis and general cognition but their relationship is unclear. In this study, we set out to clarify the relationship between the JTC bias, IQ, psychosis and polygenic liability to schizophrenia and IQ. Methods A total of 817 first episode psychosis patients and 1294 population-based controls completed assessments of general intelligence (IQ), and JTC, and provided blood or saliva samples from which we extracte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 66 publications
4
26
1
4
Order By: Relevance
“…A striking aspect of our results is that despite evident relationships between psychotic disorders and both behavioral and computational measures—and the potential for computational parameters to predict treatment outcome—we did not find any relationship between these measures and current delusions, even though these tasks were designed to assess reasoning biases thought to contribute to delusions themselves. Our findings add to a growing literature including meta-analyses, 53 large case-control, 54 and population-based studies 55 that find weak or absent correlations between delusion and beads task measures.…”
Section: Discussionsupporting
confidence: 64%
“…A striking aspect of our results is that despite evident relationships between psychotic disorders and both behavioral and computational measures—and the potential for computational parameters to predict treatment outcome—we did not find any relationship between these measures and current delusions, even though these tasks were designed to assess reasoning biases thought to contribute to delusions themselves. Our findings add to a growing literature including meta-analyses, 53 large case-control, 54 and population-based studies 55 that find weak or absent correlations between delusion and beads task measures.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, as misunderstandings of the instructions of the beads task occur more often in patients with psychosis than in healthy controls [10], they could also contribute and enlarge the frequently found group differences between patients and healthy controls. This interpretation is supported by the ndings of a large study by Tripoli et al [48], who found that the association between JTC and psychotic symptoms in patients with psychosis seems to be mediated to a large extent by IQ of the subjects. Therefore, JTC may be a consequence of more basic cognitive de cits, which may contribute to a misunderstanding of the task.…”
Section: Lack Of Associations With Psychopathologymentioning
confidence: 64%
“…Furthermore, as misunderstandings of the instructions of the beads task occur more often in patients with psychosis than in healthy controls [10], they could also contribute and enlarge the frequently found group differences between patients and healthy controls. This interpretation is supported by the ndings of a large study by Tripoli et al [48], which found that the association between JTC and psychotic symptoms in patients with psychosis seems to be mediated to a large extent by the IQ of the subjects. Therefore, JTC may be a consequence of more basal cognitive de cits, which may contribute to a misunderstanding of the task.…”
Section: Lack Of Associations With Psychopathologymentioning
confidence: 67%